CTLA4Ig-mediated blockade of T-cell costimulation in patients with psoriasis vulgaris - Judith R. Abrams; Mark Lebwohl; Cynthia Guzzo; Brian V. Jegasothy; Michael Goldfarb; Bernard S. Goffe; Alan Menter; Nicholas J. Lowe; Gerald G. Krueger; Michael J. Brown; Russell Weiner; Martin Birkhofer; et al. (1999)
Engagement of the B7 family of molecules on antigen-presenting cells with their T cell–associated ligands, CD28 and CD152 (cytotoxic T lymphocyte–associated antigen-4 [CTLA-4]), provides a pivotal costimulatory signal in T-cell activation. We investigated the role of the CD28/CD152 pathway in psoriasis in a 26-week, phase I, open-label dose-escalation study. The importance of this pathway in the generation of humoral immune responses to T cell–dependent neoantigens, bacteriophage φX174 and keyhole limpet hemocyanin, was also evaluated. Forty-three patients with stable psoriasis vulgaris received 4 infusions of the soluble chimeric protein CTLA4Ig (BMS-188667). Forty-six percent of all study patients achieved a 50% or greater sustained improvement in clinical disease activity, with progressively greater effects observed in the highest-dosing cohorts. Improvement in these patients was associated with quantitative reduction in epidermal hyperplasia, which correlated with quantitative reduction in skin-infiltrating T cells. No markedly increased rate of intralesional T-cell apoptosis was identified, suggesting that the decreased number of lesional T cells was probably likely attributable to an inhibition of T-cell proliferation, T-cell recruitment, and/or apoptosis of antigen-specific T cells at extralesional sites. Altered antibody responses to T cell–dependent neoantigens were observed, but immunologic tolerance to these antigens was not demonstrated. This study illustrates the importance of the CD28/CD152 pathway in the pathogenesis of psoriasis and suggests a potential therapeutic use for this novel immunomodulatory approach in an array of T cell–mediated diseases.